Effects of Fertilizers on Growth and Sclerotia Formation of Macrophomina Phaseolina (Tassi) Goid. (Bangladesh Journal of Botany, 2021)
Macrophomina phaseolina was exposed to various concentrations of N, P and K fertilizers in PDA medium. Most of the fertilizers did not affect and some slightly increased the mycelial growth. All the fertilizers significantly affected sclerotia of the fungus. Urea and CAN at 10 ppm N reduced sclerotia by 85 to 90%. Similar reduction was noted with ammonium sulfate and NPK-(20 : 20 : 20) at or above 20 ppm N. DAP decreased sclerotia count whereas SSP increased it up to 300%. Under the influence of potassium fertilizers sclerotia count was increased by 200 to 400%, maximum with potassium nitrate followed by MOP and SOP.Bangladesh J. Bot. 50(2): 413-416, 2021 (June)